Genetic analysis and molecular resistance to race 2 of Fusarium wilt in pigeonpea [Cajanus cajan (L.) Millsp.]. (October 2017) - Patil, Prakash G.; Bohra, Abhishek; Dubey, Jyotirmay; Saabale, Parasappa R.; Mishra, Raj K.; Pandey, Gaurav; Das, Alok; Rathore, Meenal; Singh, Farindra; Singh, Narendra Pratap
Abstract: The long-stagnated productivity of pigeonpea may be attributed to its vulnerability to several diseases of which vascular wilt caused by Fusarium udum Butler is of paramount significance. Disease management approaches that rely on chemicals are not very appropriate especially in view of rising environmental concerns and resource poor nature of marginal farmers. Therefore, deploying host plant resistance in genetic improvement schemes through molecular tagging of underlying resistance genes is central to resistance breeding. To this end, here we offer SSR markers for resistance to race 2 of Fusarium wilt (FW) in KPL 43 (resistant) through bulked segregant analysis (BSA). The analysis of disease incidence data on 271 F2 individuals derived from Bahar (susceptible) × KPL 43 (resistant) revealed the involvement of two or more recessive genes (1:15) with duplicate dominant epistasis. Marker polymorphism survey using 270 hypervariable pigeonpea-specific SSR markers (HASSRs) yielded 115 polymorphic markers (42.6%) between the parents. SSR markers HASSR8190, HASSR58180 and HASSR121170 differentiated resistant and susceptible bulks. A joint segregation analysis between the each marker with FW resistance in F2 population supported the linkage between FW and the SSRs. Recessive class analysis (RCA) based on genotypic data of ten resistant F2 individual also confirmed linkage between SSRs and FW resistance gene. The independent assortments was observed between the pair of associated SSR markers, and this corroborated with the alignment of these three SSR markers on three different chromosomes in the pigeonpea genome. The association of SSR markers HASSR8190 and HASSR58180 with FW resistance was further validated in a panel of 89 pigeonpea genotypes through single marker analysis (SMA) and Kruskal Wallis test. Given the recessive nature of the genes conferring FW resistance, these SSR markers have tremendous implications for breeding FW resistant pigeonpea genotypes. Highlights: Genetic inheritance for resistance to race 2 of Fusarium wilt (FW) revealed two or more recessive genes for resistance in KPL 43 (resistant). Bulked segregant analysis identified three SSR markers HASSR8190, HASSR58180 and HASSR121170 associated with resistance to FW race 2. Linkage between SSR markers and FW resistance gene(s) was confirmed through analysis of genotypic and phenotypic data of 271 F2 individuals. Based on recessive class analysis (RCA), we found HASSR8190 as the most closely linked (5.01 cM) with the FW resistance gene, followed by HASSR121170 (10.13 cM), and HASSR58180 (27.46 cM). Association of SSRs with FW resistance gene(s) was further validated in a panel of 89 pigeonpea genotypes through single marker analysis (SMA) and Kruskal Wallis test.